Scythian zoonyms in the Hesychian lexicon - Witczak, Krzysztof Tomasz (Papers in Linguistics, 2023)
The article discusses seven Scythian glosses preserved in the lexicon of Hesychius of Alexandria (5th–6th AD), which refer to the domesticated animals or the East European wild fauna. Four among the analysed zoonyms have a confirmed Scythian origin (explicitly indicated by the Greek lexicographer), whereas two (ἀρανίς · ἔλαφος “aranis – deer”; γοῖτα· οἶς “goita – sheep”) are attributed to the Scythian vocabulary based on a reasonable conjecture. The seventh gloss concerns a typical Scythian drink obtained from a mare’s milk. A meticulous analysis of lexical data makes it possible to determine clearly the etymology of three Scythian names for domesticated animals, namely sheep, dog and mare, cf. Scyth. γοῖτα ‘sheep’ (< Iran. *gaiθā- ‘flock of sheep’); Scyth. παγαίη ‘dog’ (< *spakai̯ā-← Iran. *śaka- m. ‘dog’); Gk. ἱππάκη f. ‘mare’s milk drink’ (← Scyth. *appākā ← Scyth. *appā- f. ‘mare’ < *aspā- < Iran. *aśā- f. ‘id.’). Additionally, Hesychius of Alexandria noted four Scythian terms for wild animals, namely reindeer (or moose), deer, swan and locust, cf. Scyth. τάρανδος ‘reindeer or moose’ (← Finno-Ugric *ćar/ań/ta ‘reindeer / moose’); Scyth. ἀρανίς ‘deer, stag’ (< Iran. *araniš, cf. Lith. elenìs, élnis ‘deer’); Scyth. ἄγλυ ‘swan’ (< Iran. *madgu- ‘a species of water bird’); Scyth. ἀδιγόρ ‘locust’ (< Iran. *atahī-gar/a/-, originally ‘devouring the grass’).